Model of COVID-19 Spread Control Using the Dynamic System Approach in West Nusa Tenggara Province, Indonesia - Anwar, Hairil; Sukardi, L. (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The objective of this research is to try to conduct an outbreak modeling of a Corona virus (Covid-19) pandemic in West Nusa Tenggara (NTB) Province. The modeling approach used in this study is through dynamic system approach with the SEIR technique (Susceptible - Exposed - Infectious - Recovered). In this model, the effectiveness of the policy is tested on three policy scenarios, namely: (1) Loose Scenario is the effectiveness of the intervention 0 - 30%; (2) Moderate Scenarios is the effectiveness of interventions 31 - 60%; and (3) Strict Scenarios is the effectiveness of interventions > 61%. The dynamic model with the Susceptible - Exposed - Infectious - Recovered (SIER) technique can reasonably project the spread of Covid-19. The scenarios of policy interventions that can be implemented to overcome the spread of Covid-19 in West Nusa Tenggara Province are moderate scenario and strict scenario.